2010
DOI: 10.1590/s0103-90162010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to oat crown rust in recombinant inbred lines

Abstract: Crown rust is the main disease affecting oats (Avena sativa L.), and genetic resistance has been the chief method utilized to control this disease. A population composed of 135 recombinant inbred lines, F5:6, generated by crossing the oat cultivar UFRGS 8 with the genotype Pc68/5*Starter, was assessed on the inheritance of resistance to crown rust (Puccinia coronata f. sp. avenae P. Syd. & Syd.). The evaluation of resistance in F5:6 seedlings was based on the type of infection resulting from inoculation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…The virulence of P. coronata isolates from southern Brazil towards the Pc68 gene conferring resistance to P. coronata in oat genotype Pc68/5*Starter has previously been reported by Leonard and Martinelli (2005) and Graichen et al (2010). This oat genotype shows no disease in the early stages of development but pustules are present after flowering at the end of the plant growth cycle.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The virulence of P. coronata isolates from southern Brazil towards the Pc68 gene conferring resistance to P. coronata in oat genotype Pc68/5*Starter has previously been reported by Leonard and Martinelli (2005) and Graichen et al (2010). This oat genotype shows no disease in the early stages of development but pustules are present after flowering at the end of the plant growth cycle.…”
Section: Discussionmentioning
confidence: 67%
“…where: y i = % leaf area affected by crown rust (severity at the i th observation; t i = time in days after sowing at the i th observation, n = period of days from the onset and latest assessment of the disease, and c = the longest epidemic period among the genotypes tested (from Graichen et al 2010). …”
Section: Field Experimentsmentioning
confidence: 99%
“…The relationship between crown rust resistance in oat and Pca virulence displays typical gene‐for‐gene characteristics, with resistance conferred by multiple single dominant resistance genes, each displaying different specificities towards pathogen isolates (Chong et al ., ). To date, more than 100 crown rust resistance ( Pc ) genes have been described in oat (Table S1, see Supporting Information) (Gnanesh et al ., ; Graichen et al ., ; Tan and Carson, ; USDA‐ARS CDL, ), although the lack of molecular information makes it difficult to determine whether some of these genes may be the same or are alleles at a common locus. In contrast with this wealth of R genes, no effectors have yet been identified in Pca , and the knowledge of rust pathogen Avr proteins remains limited to Melampsora lini , the causal agent of flax rust, and Hemileia vastatrix , the causal agent of coffee leaf rust (Maia et al ., ; Ravensdale et al ., ).…”
Section: Pathogenicity and Population Biology Of Pcamentioning
confidence: 99%
“…The area under the disease progress curve (AUDPC) was estimated by the trapezoidal integration of the curve for each individual plant from the six basic generations. The AUDPC values were normalized and corrected (AUDPCnc) by dividing the values by the number of days until the final severity reading for each genotype and multiplying the resulting values by the number of days until the final severity evaluation of the experiment, according to Graichen et al (2010), as shown below:…”
Section: Plant Materialsmentioning
confidence: 99%
“…With respect to the predominant oat rust races that are found in Brazil, the most promising resistance gene is Pc68, due to the low incidence of virulent pathotypes that have been found to affect it (Leonard and Martinelli 2005). However, Graichen et al (2010) reported that the resistance that is provided by Pc68 has been overcome in Brazil. Unfortunately, the effectiveness of genes that provide specific resistance to P. coronata f.sp.…”
Section: Introductionmentioning
confidence: 99%